OPTIMASI UMUR KALUS SEBAGAI DONOR SEL TERHADAP BIOMASSA DAN KADAR SAPONIN PADA KULTUR AGREGAT SEL Talinum paniculatum (Jacq) Gaertn - Agus Muji Santoso (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
This study was aimed to explore the age appropriate of callus which forming cell suspension in liquid culture. T. paniculatum leaf explants planted on solid MS medium with the addition of 2 ppm of 2,4 D and 1 ppm kinetin. Callus was on 3, 4, 5, and 6 weeks moved separately in 50 mL of liquid MS with 1 ppm 2,4 D and 1 ppm kinetin, agitated at 100 rpm for six days in absolute dark conditions (25 ± 1oC). Dry biomass and total saponins were measured by the Hu method. Callus on 4-week-old callus has the highest biomass (0.16 x 10-3 g), but the highest levels of saponins derived callus at the age of 5 weeks (17.45 ppm). Keywords: biomassa, callus age, total saponin, Talinum paniculatum, cell agregat